Elements of phase transitions and critical phenomena - Nishimori, Hidetoshi; Ortiz, Gerardo (Oxford : Oxford University Press, 2011)
An introductory account of the theory of phase transitions and critical phenomena, this book reflects lectures given by the authors to graduate students at their departments and is thus classroom-tested to help beginners enter the field.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Phase transformations (Statistical physics); Critical phenomena (Physics)